Access to Justice for Black Inventors - Goodman, Jordana R; Patterson, Khamal (Vanderbilt law review, 2024)
To receive a patent, an inventor must meet certain inventive and procedural standards. Their invention must be novel, nonobvious, and written in such a way that any person skilled in the inventive subject can make and use the invention without undue experimentation. This process is far from objective.